The role of receivership in Malaysian corporate insolvency framework - Ooi, Zi Jie (Fakulti Undang-Undang, Universiti Kebangsaan Malaysia, 2021)
UK and US legislators shows an inherent divide on the understanding of the purpose of insolvency law. US scholars agreed with corporate insolvency law’s role in maximising value; while UK scholars concern itself with how value is distributed. We find this departure stems from the unique finance structure of two countries. Under Corporate Law Reform Committee’s recommendation, two clarification of laws are made: (1) receivers now are agent of appointed company without fiduciary duties (2) appointment of liquidator does not vacate receiver’s office. Receiver now can contract on behalf of the company without incurring liability. Receiver is generally perceived as a financial priest that administer the business’s last rites. It is popular perception that receivers hold too much power. In contrary to general conception, we are against the case for receivership law reform. Rather, we argue that creditors and debtors should practice receivership with two aims: (1) to reduce monitoring cost of creditors, in turn reduce debt interest (2) to maximise the value of the company as a whole. Creditor’s race to appoint receiver is a zero-sum game which benefits no one. Nash equilibrium finds rearrangement to be preferable when there exists more than one secured creditor.